2007
DOI: 10.1093/hmg/ddm160
|View full text |Cite
|
Sign up to set email alerts
|

A stop codon mutation in SCN9A causes lack of pain sensation

Abstract: The general lack of pain experience is a rare occurrence in humans, and the molecular causes for this phenotype are not well understood. Here we have studied a Canadian family from Newfoundland with members who exhibit a congenital inability to experience pain. We have mapped the locus to a 13.7 Mb region on chromosome 2q (2q24.3-2q31.1). Screening of candidate genes in this region identified a protein-truncating mutation in SCN9A, which encodes for the voltage-gated sodium channel Na(v)1.7. The mutation is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(124 citation statements)
references
References 24 publications
6
118
0
Order By: Relevance
“…Loss-of-function mutations in hNa V 1.7 cause a congenital indifference to pain with no other sensory impairments except anosmia (8,22,23), whereas gain-offunction mutations are associated with painful neuropathies (7,24). Ablation of Na V 1.7 in all mouse sensory neurons abolishes mechanical pain, inflammatory pain, and reflex withdrawal responses to heat, without affecting neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function mutations in hNa V 1.7 cause a congenital indifference to pain with no other sensory impairments except anosmia (8,22,23), whereas gain-offunction mutations are associated with painful neuropathies (7,24). Ablation of Na V 1.7 in all mouse sensory neurons abolishes mechanical pain, inflammatory pain, and reflex withdrawal responses to heat, without affecting neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…A different set of gain-of-function mutations that impair inactivation of Na V 1.7 and in some cases produce a persistent current (Fertleman et al, 2006;Dib-Hajj et al, 2008;Jarecki et al, 2008) has been linked to a different, nonoverlapping syndrome, paroxysmal extreme pain disorder (PEPD), characterized by paroxysmal episodes of burning pain in the rectal, ocular, and mandibular areas accompanied by autonomic manifestations such as skin flushing (Fertleman et al, 2006). In contrast, loss-of-function mutations of Na v 1.7 have been linked to congenital inability to experience pain (Cox et al, 2006;Ahmad et al, 2007;Goldberg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The link between Na V 1.7 functional change and pathogenesis Previous studies have concluded that pain-insensitive mutations are due to a total loss of Na V 1.7 channel function (Cox et al, 2006(Cox et al, , 2010Ahmad et al, 2007), which, given the fundamental role of Na V 1.7 in regulating electrical activity in sensory neurons, intuitively explains the painless phenotype. Here, however, we present three novel CIP-associated mutations in Na V 1.7 that all retain some functionality.…”
Section: Discussionmentioning
confidence: 99%